Some evidence of environmental reporting by Shari'ah compliant companies in Malaysia - Annuar, Hairul Azlan; Sulaiman, Maliah; Nik Ahmad, Nik Nazli (International Islamic University, 2009)
Our study examines environmental disclosure practices of SharÊcah approved companies. The study investigates the extent SharÊcah approved companies report on the environment and compares this with non-SharÊcah approved companies. We also examine four variables that may influence the level of environmental disclosure in SharÊcah approved companies: size, number of Muslim directors, impact the activities of the company has on the environment (environmental sensitivity) and profitability of the company. Results provide some evidence that SharÊcah approved companies have a higher level of environmental disclosure. Further, size and environmental sensitivity, unlike profitability, do not affect the level of environmental disclosure of SharÊcah approved companies. These findings are inconsistent with the results of prior studies (Berthelot et al., 2003; Deegan and Gordon, 1996). The study makes an important contribution to the literature as there is a paucity of research which examines the influence of religion, in general, and Islam, in particular, on the extent of environmental disclosure.